2021
DOI: 10.1111/pai.13440
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of cow’s milk allergy and the development of atopic diseases into adulthood

Abstract: Cow's milk allergy (CMA) is the most common food allergy in infants, with incidence rates estimated between <1% and 3%. [1][2][3][4][5][6][7][8] The majority of infants with CMA develop symptoms in early infancy, 1,2 and onset after 12 months of age is rare. 3 Allergic reactions to cow's milk (CM) are often IgE-mediated, causing cutaneous, gastrointestinal, and respiratory symptoms. 2,3,5 CMA manifestations may vary from IgE-mediated to non-IgE-mediated reactions. A differentiation between IgE-mediated and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Whilst a proportion of eczema cases may be non‐atopic, 30 there is a greater prevalence of CMA among children with infantile eczema 31 . Similarly, atopic dermatitis may present in 11%–20% of children in the United Kingdom, 32 and has been found to be more common in children with CMA than those without 33 . The presentation of these symptoms in children with and without CMA may lead to challenges with differential diagnosis in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a proportion of eczema cases may be non‐atopic, 30 there is a greater prevalence of CMA among children with infantile eczema 31 . Similarly, atopic dermatitis may present in 11%–20% of children in the United Kingdom, 32 and has been found to be more common in children with CMA than those without 33 . The presentation of these symptoms in children with and without CMA may lead to challenges with differential diagnosis in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In addition, studies were mostly focusing on the development of respiratory diseases in risk populations and cross-sectional studies were largely lacking. 4 We highlight here as editor's choice the recent study by Strachan and colleagues, which aimed to update trends in prevalence of symptoms of childhood allergic respiratory diseases and compare them with data from 15 to 23 years ago. 5 Data of symptoms suggesting allergic rhinitis and conjunctivitis by standardized questionnaires were collected from over 100,000 participants.…”
mentioning
confidence: 99%
“…By conducting a DBPCFC test, the study found that dermatological symptoms of urticaria, erythematous rash, and angioedema were noted primarily in the immediate hypersensitivity reaction group (62.5% of participants with CMA), whereas gastrointestinal symptoms were noted in the delayed-type hypersensitivity group (28.8% of participants with CMA) [23]. However, more recent studies have shown dermatological manifestations occurring within both mechanisms [24]. Interestingly, type I-mediated reactions were found to occur more frequently within infant and children populations.…”
Section: Review Type I Hypersensitivity Reactions and Atopic Dermatitismentioning
confidence: 99%